The Identification of Host Proteins That Interact with Non-Structural Proteins-1α and -1β of Porcine Reproductive and Respiratory Syndrome Virus-1 - Sofia Riccio; Kay Childs; Ben Jackson; Simon P. Graham; Julian Seago (Viruses, 2023)
Porcine reproductive and respiratory syndrome viruses (PRRSV-1 and -2) are the causative agents of one of the most important infectious diseases affecting the global pig industry. Previous studies, largely focused on PRRSV-2, have shown that non-structural protein-1α (NSP1α) and NSP1β modulate host cell responses; however, the underlying molecular mechanisms remain to be fully elucidated. Therefore, we aimed to identify novel PRRSV-1 NSP1–host protein interactions to improve our knowledge of NSP1-mediated immunomodulation. NSP1α and NSP1β from a representative western European PRRSV-1 subtype 1 field strain (215-06) were used to screen a cDNA library generated from porcine alveolar macrophages (PAMs), the primary target cell of PRRSV, using the yeast-2-hybrid system. This identified 60 putative binding partners for NSP1α and 115 putative binding partners for NSP1β. Of those taken forward for further investigation, 3 interactions with NSP1α and 27 with NSP1β were confirmed. These proteins are involved in the immune response, ubiquitination, nuclear transport, or protein expression. Increasing the stringency of the system revealed NSP1α interacts more strongly with PIAS1 than PIAS2, whereas NSP1β interacts more weakly with TAB3 and CPSF4. Our study has increased our knowledge of the PRRSV-1 NSP1α and NSP1β interactomes, further investigation of which could provide detailed insight into PRRSV immunomodulation and aid vaccine development.